Strengthening the Statistical System for National Development: A Case Study of Pakistan - Wattoo, Muhammad Razzaq Aman (Journal of Public Policy Practitioners, 2025)
An integrated, updated, digitized, and comprehensive statistical system is the core of a country’s development. Such a system helps to determine population size, poverty levels, employment, health, education, and other resources (human and non-human). Pakistan’s statistical system is deficient in many core areas; therefore, it lacks reliability and remains weak. This weakness results in ineffective planning and mismanagement of resources. The current study brought forth some of the weak areas of the statistical system by conducting a review of grey literature. It suggested engagement of local institutions as well as their digitization and integration, creating a single database for accuracy and transparency for efficient national resource utilization.